(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Article 4.3 of the WADA International Standard for Therapeutic Use Exemptions (ISTUE) 2019 edition provides four alternative reasons for the retroactive Therapeutic Use Exemption (TUE) that an athlete can prove. One amongst them is a “fairness criterion”, applying when other criteria could not be meet in case of the sportsmen. The process of obtaining the retroactive TUE on fairness criterion raises a question in context the “fair” and “unfair”. This dilemma could raise the ground of factual circumstances in the particular case of an anti-doping violation. When the sportsman does not have any other criterion for the retroactive TUE, he or she may attempt to argue the fairness in the occasion. Although the Anti-Doping Organizations have the right to decide the content of “fairness”, is it impossible for the Court of Arbitration for Sport (CAS) as a non-professional body on medical issues? The WADA regulations give us another example of using fairness as a turning point in cases of sportsman’s anti-doping compliance procedures. Thus the articles 10.8 and 10.11.3.4 of the WADA Code 2015 are used as the “fairness exception” for excluding the presumption of disqualifying the sportsmen’s results, points, medals, and prizes in case of anti-doping liability. To understand what the “fairness” is in cases of anti-doping offenses we turn our view on the CAS practice on issues of the “fairness exception” and “fairness criterion”. In conclusion, we could summarize the CAS approaches to the content of fairness in cases, connected with the process of granting the retroactive TUE.